Mutations in mammalian target of rapamycin regulator DEPDC5 cause focal epilepsy with brain malformations. Issue 5 (14th April 2014) - Scheffer, Ingrid E.; Heron, Sarah E.; Regan, Brigid M.; Mandelstam, Simone; Crompton, Douglas E.; Hodgson, Bree L.; Licchetta, Laura; Provini, Federica; Bisulli, Francesca; Vadlamudi, Lata; Gecz, Jozef; Connelly, Alan; et al.
<x xml:space="preserve">Abstract</x> We recently identified DEPDC5 as the gene for familial focal epilepsy with variable foci and found mutations in >10% of small families with nonlesional focal epilepsy. Here we show that DEPDC5 mutations are associated with both lesional and nonlesional epilepsies, even within the same family. DEPDC5‐associated malformations include bottom‐of‐the‐sulcus dysplasia (3 members from 2 families), and focal band heterotopia (1 individual). DEPDC5 negatively regulates the mammalian target of rapamycin (mTOR) pathway, which plays a key role in cell growth. The clinicoradiological phenotypes associated with DEPDC5 mutations share features with the archetypal mTORopathy, tuberous sclerosis, raising the possibility of therapies targeted to this pathway. Ann Neurol 2014;75:782–787